Bioelectrical impedance analysis in assessing the chances of obtaining coronary heart disease in obese subjects - Mohktar, M.S.; Ibrahim, F.; Ismail, N.A. (2005)
This paper describes parameters to predict the chances of obtaining coronary heart disease (CHD) using bioelectrical impedance analysis (BIA) in obese subjects at the University of Malaya Student Health Clinic (UMHC), Kuala Lumpur. Bioelectrical impedance measurements were conducted on 88 subjects (30 males and 58 females) with mean body mass index (BMI) of 30kg/m2. We investigated all the parameters in BIA, patients' lipid profiles and demographic data in explaining of getting CHD incidences. The lipid profiles include serum total cholesterol, low density lipoprotein (LDL) cholesterol, high density lipoprotein (HDL) cholesterol, and the total cholesterol and HDL cholesterol ratio. In this prediction, 7 predictors (height, weight, body capacitance, fat mass, extra cellular mass and body cell mass ratio, basal metabolic rate, and intracellular water) were found to be significant for predicting CHD incidence in obese subjects. These variables explain approximately 68.3 of the variation of CHD incidence in obese subjects. Â© 2005 IEEE.